Penerapan Garis Bilangan Riil dalam Memahami Konsep Dasar Nilai Mutlak - Prihaten Maskhuliah; Salwa Rifdah Rizqullah; Sarmila Sarmila (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Absolute value is a fundamental mathematical concept that supports advanced topics, including algebra, calculus, and numerical analysis. Although often regarded as simple, absolute value involves considerable conceptual complexity. Many students develop misconceptions because conventional instruction tends to emphasize procedures rather than meaning. As a result, students often understand absolute value only as a rule for positive numbers or as a way to remove a minus sign. This limited understanding causes difficulty, confusion, and errors when students encounter formal definitions, absolute value equations, inequalities, and complex mathematical models. Therefore, this qualitative literature study aims to describe the use of the real number line as a concrete visual representation that can bridge the abstract nature of absolute value. The study was conducted through an in-depth review of literature, articles, textbooks, and previous research findings. The results indicate that a visual approach using the real number line is effective in developing students’ intuition. Through this representation, absolute value can be interpreted as distance. In a single-point context, the symbol represents the number of steps from the position of x to the reference point zero. In a two-point context, subtraction can be represented as the distance between two points, such as the distance from point A to point B. This distance-based approach also helps students understand the commutative property of absolute value logically and reduces calculation errors caused by reliance on formal formulas. Overall, the real number line can reduce procedural misconceptions and promote a complete, meaningful, and durable conceptual understanding of absolute value.